Design of a voice control system for a machine or robot - Abdelghani Elalouani; Kamel Elalouani; Koribaa Mustapha (Université Amar Thelidji- Laghouat FACULTE: DE TECHNOLOGIE DEPARTEMENT : D’ELECTRONIQUE, 2021)
“In this project we are interested in the design of an automatic voice commands system which allows us to transfer commands to a machine or robot arm using microcomputer, this system can be used by people who can’t use keyboard or mouse to give simple commands to a computer due to a physiological disability or someone his hands are in operating conditions. The mathematical tools to be employed in this system are the Hidden Markov Models (HMM), its models are generally used for the processing of random physical signals with sequential nature vis-à-vis the information they conduct in this case is speech signal.”
Key words: HTK, HMM, HTK Toolkit, voice commands, Voice Signal, Speech recognition, Speech Production.